Redemption : the last battle of the Civil War - Lemann, Nicholas (Farrar, Straus and Giroux, 2006)
A century after Appomattox, the civil rights movement won full citizenship for black Americans in the South. It should not have been necessary: by 1870 those rights were set in the Constitution. Journalist Lemann describes an insurgency that changed the course of American history: from 1873 to 1877 white Southern Democrats waged a campaign of political terrorism to create chaos and keep blacks from voting out of fear for their lives and livelihoods, aiming to overturn the Fourteenth and Fifteenth Amendments and challenge President Grant's support for the emergent structures of black political power. The remorseless strategy of well-financed "White Line" organizations culminated in a bloody, corrupt election in which Mississippi was "redeemed"--That is, returned to white control. This led to the death of Reconstruction--and of the constitutional rights of the former slaves. We are still living with the consequences.--From publisher description.